Forgotten customers, inclusive customers: personal values and coproduction of physically disabled persons in leisure consumption - Nuno Álvares Felizardo Jr; Irene Raguenet Troccoli; Patrícia Leite da Silva Scatulino (Tourism & Management Studies)
Physically disabled customers (PDCs) in Brazil face numerous obstacles in their social role as consumers, in spite of their significant share of the population. Their low visibility implies they are not seen for what they really are: potential consumers. Consequently, they often cannot satisfy their wishes or achieve personal values through the acquisition of products and services. This suggests an investigation of the major reasons behind their consumption practices related to personal values. Using the soft laddering technique, this study shows that happiness and freedom are the personal values achieved by PDCs while enjoying beachside recreation activities. Non-participant observation and the priming stimulus of the five human senses were simultaneously used to investigate the intersection of these values with the stimuli offered by the service providers to these customers to co-produce the service. Finally, further investigation is suggested as to why, contrary to common sense, social belonging was not one of the personal values identified.